Fostering synergy between cell biology and systems biology. Issue 8 (August 2015) - Eddy, James A.; Funk, Cory C.; Price, Nathan D.
Highlights Cell and systems biology share a goal in understanding the mechanisms of cell function. Systems biology provides tools to study complex cellular processes at larger scales. Iteration between model building and experiment yields contributions to cell biology.